Coagulation disorders in patients with femoral head osteonecrosis - Garcia, Flávio Luís (Brazilian Society of Orthopedics and Traumatology, 2013)
OBJECTIVE: To compare the occurrence of thrombophilic disorders in patients with idiopathic osteonecrosis of the femoral head and patients with secondary osteonecrosis of the femoral head. METHODS: Twenty-four consecutive patients were enrolled, with eight of them presenting idiopathic osteonecrosis and 16 presenting secondary osteonecrosis. The tests for detection of thrombophilic disorders were measurements of protein C, protein S and antithrombin levels and detection of prothrombin and factor V gene mutations. We compared the results using the odds ratio statistics for the thrombophilic disorders between the two groups. RESULTS: The odds ratio for the protein S deficiency and protein C deficiency between the idiopathic and secondary groups were 5 and 2.14, respectively. Thus, an individual with idiopathic osteonecrosis has 5 times more chance of presenting protein S deficiency and 2.14 times more chance of presenting protein C deficiency than an individual with secondary osteonecrosis. CONCLUSION: Patients with idiopathic osteonecrosis have more chances of presenting thrombophilias than those with secondary osteonecrosis, suggesting these coagulation disorders can play an important role in the pathogenesis of the osteonecrosis in cases where there was no initial risk factor recognized. Level of Evidence III, Case-Control Study.